Women Farmers and Climate Adaptation in Bihar’s Rice Systems: A Policy Brief - Munshi, Sugandha; Samaddar, Arindam; Srivastava, Amit; Patil, Vikram; Peramaiyan, Panneerselvam; Kumar, Virender (International Rice Research Institute, 2025)
Key Messages • Women farmers in Bihar are facing a heavier burden from climate change. They are increasingly managing farm work, including nursery planting, transplanting, and harvesting, often because male family members have migrated for work. This adds to their existing household responsibilities. • The primary barrier to successful climate adaptation is not a lack of awareness, but a lack of access to essential resources. As one-woman farmer from Nalanda stated, “Women do a lot in agriculture. Much more than men do. For example, we lay water pipes in the field for irrigation too and can fold them back”. • Self-Help Groups (SHGs), particularly those part of the JEEViKA network, have become the most important local institutions for resilience. Women use these groups to access loans, share irrigation pumps, run joint nurseries, and exchange trusted information. • A Jeevika farmer from Samastipur explained this dynamic: “We both make decisions together, but he goes out more, so he knows more. Sometimes I share what I learn from my SHG… and then he listens”. • Policy can be most effective by shifting from a gender-neutral approach to a gender-responsive one. Investing in women’s access to water, finance, and information through established SHG platforms is a practical and efficient path to equitable climate adaptation.